2011
DOI: 10.1080/17565529.2011.599550
|View full text |Cite
|
Sign up to set email alerts
|

New and additional to what? Assessing options for baselines to assess climate finance pledges

Abstract: All major climate policy agreements-the UN Framework Convention, the Kyoto Protocol, and recently the Cancun Agreements-have stated that climate finance for developing countries will be "new and additional". However, the term "new and additional" has never been properly defined. Agreeing a system to measure a baseline from which "new and additional" funding will be calculated will be central to building trust and realising any post-Kyoto agreement. We explore eight different options for a baseline, and assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Under the UNFCCC process developed country governments have pledged to mobilise substantial capital, both public and private investments, over the short (Stadelmann, Timmons Roberts and Michaelowa, 2011b) and medium term (Timmons Roberts, Stadelmann and Huq, 2010). By 2020 $100 billion per year should be invested from developed country finance into developing country projects.…”
Section: Clean Energy Investingmentioning
confidence: 99%
“…Under the UNFCCC process developed country governments have pledged to mobilise substantial capital, both public and private investments, over the short (Stadelmann, Timmons Roberts and Michaelowa, 2011b) and medium term (Timmons Roberts, Stadelmann and Huq, 2010). By 2020 $100 billion per year should be invested from developed country finance into developing country projects.…”
Section: Clean Energy Investingmentioning
confidence: 99%
“…The principle of additionality was included in the Convention (UNFCCC 1992: Article 4(3)) due to the concerns of developing countries that developed countries would divert funds for climate finance from existing flows of development finance. Yet there is no agreed upon baseline against which additionality can be measured (Stadelmann et al 2011).…”
Section: Fragmentation Across the System And Over Timementioning
confidence: 99%
“…The scant literature on contributor nations' approaches to climate finance mostly seeks to map and compare existing policies and programs, either for climate finance as a whole (Stadelmann, 2012;Buchner et al, 2011Buchner et al, , 2012, or on particular policy issues faced by contributors such as additionality (Stadelmann et al, 2011) and methods for classifying aid activities as climate-related . The literature highlights considerable diversity among contributors on key policy issues and institutional arrangements for delivering climate finance, including effort-sharing, understandings of additionality, allocation priorities and choices about delivery channels, and financing instruments.…”
Section: Inter-agency Dynamics In Governing International Funding Commentioning
confidence: 99%
“…Despite some comparative analysis of contributors' positions on aspects of climate finance (e.g. Michaelowa and Michaelowa, 2011;Stadelmann et al, 2011Stadelmann et al, , 2012, little is known about variations in inter-agency configurations within individual contributing governments that may have influenced those positions. Nor-despite the fact that contributors count the bulk of their climate finance as aid-has existing research systematically identified the specific dimensions along which contributors' climate finance and aid practices 2 align or differ.…”
mentioning
confidence: 99%
See 1 more Smart Citation